Implementasi Kegiatan Bakti Sosial Bersama Masyarakat Desa Klumpang Kampung Sebagai Wujud Kepedulian Cinta Lingkungan - Desi Arni Syahfitri; Siti Nurcahayati; Khairunnisa Sitompul; Hera Hazira Herdina Lubis; Salsabila Mayla; Ainun Meryna Aulia; Nadiyah Mawaddah; Ika Safitri; Indah Putri Maharaja; Nurul Wardani Fadhilah Lubis; Chuzaimah Batubara (CV. Multi Kreasi Media, 2025)
Community Service Program (KKN) is a form of community service activity conducted by universities by students under the guidance of lecturers and local government leaders. Through KKN, students can apply the knowledge they have gained in higher education to real life. KKN students from the State Islamic University of North Sumatra Medan who were stationed in Klumpang Kampung Village created a work program in the form of Community Service activities. The results of this community service show that the waste problem in Klumpang Kampung Village is a serious issue with a dirty environment, especially around the river near residential areas. Public awareness of cleanliness and health is important to prevent disease and potential flooding due to piles of garbage that can clog water channels during the rainy season. This Community Service Program is not only carried out to maintain the cleanliness of the village, but also as a medium to get closer to the people of Klumpang Kampung Village and to maintain harmony between communities. In this case, certain agendas are needed in Klumpang Kampung Village, so as to strengthen the existing family ties and also create a spirit of mutual reminder between the community about the importance of cleanliness and health, as well as providing a place as a final disposal for waste. The increasingly better quality of clean and healthy life of the people of Klumpang Village will have an impact on other village communities.